Processes for evidence summarization for patient decision aids: A Delphi consensus study - Scalia, Peter; Saunders, Catherine H; Dannenberg, Michelle; MC Giguere, Anik; Alper, Brian S; Hoffmann, Tammy; Perestelo‐Perez, Lilisbeth; Durand, Marie‐Anne; Elwyn, Glyn (Health expectations : an international journal of public participation in health care and health policy, 2021)
Background Patient decision aids (PDAs) should provide evidence‐based information so patients can make informed decisions. Yet, PDA developers do not have an agreed‐upon process to select, synthesize and present evidence in PDAs. Objective To reach the consensus on an evidence summarization process for PDAs. Design A two‐round modified Delphi survey. Setting and participants A group of international experts in PDA development invited developers, scientific networks, patient groups and listservs to complete Delphi surveys. Data collection We emailed participants the study description and a link to the online survey. Participants were asked to rate each potential criterion (omit, possible, desirable, essential) and provide qualitative feedback. Analysis Criteria in each round were retained if rated by >80% of participants as desirable or essential. If two or more participants suggested rewording, reordering or merging, the steering group considered the suggestion. Results Following two Delphi survey rounds, the evidence summarization process included defining the decision, reporting the processes and policies of the evidence summarization process, assembling the editorial team and managing (collect, manage, report) their conflicts of interest, conducting a systematic search, selecting and appraising the evidence, presenting the harms and benefits in plain language, and describing the method of seeking external review and the plan for updating the evidence (search, selection and appraisal of new evidence). Conclusion A multidisciplinary stakeholder group reached consensus on an evidence summarization process to guide the creation of high‐quality PDAs. Patient contribution A patient partner was part of the steering group and involved in the development of the Delphi survey.